Investigating the kinetics of tannin removal in Sorghum [Sorghum bicolor (L.) Moench] grains through a soaking process - Bahlawan, Zuhriyan Ash Shiddieqy; Kumoro, Andri Cahyo; Wahono, Satriyo Krido; Megawati, .; Ping, Tan Chin; Rizal, Wahyu Anggo (Gadjah Mada University, 2025)
Sorghum (Sorghum bicolor (L.) Moench) grains contain tannins that significantly affect their nutritional value and potential utilizations in food product development. This study aims to investigate the kinetics of tannin removal during the soaking process and to optimize the operating condition. To achieve the goals, sorghum grains were subjected to various soaking durations, temperatures, and soaking solution concentrations. The soaking process employed potassium hydroxide and calcium hydroxide solutions at concentrations ranging from 0.05% to 0.15%; soaking temperatures were varied at 30°C, 40°C, and 50°C. Soaking was performed for 8 hours, with samples withdrawn every hour. The dissolved tannin was analyzed for its concentration, and the data were fitted to first-order rate equation kinetic models to determine the rate constants associated with tannin reduction. This study provides valuable insights into the soaking kinetics of sorghum grains, highlighting the potential for improving sorghum-based products’ nutritional quality through optimized soaking treatments. From the investigation results, the type and concentration of the solvent, as well as the soaking temperature, affected the tannins removal rate from sorghum grains. The highest dissolution rate and constant (k) were obtained during soaking in 0.15% calcium hydroxide solution at 50°C, with values of 0.436 ppm. min⁻¹ and 0.00616 min⁻¹, respectively. The average percentage error of the first-order reaction kinetics model was below 0.2%, which suggested its high suitability for application in the soaking process of sorghum grains using an alkaline solvent. The findings can guide food processors in developing more efficient methods for tannin reduction, enhancing the utilization of sorghum as both a staple food and food ingredient.